Antifungal properties of grape seed extract on various species of Candida organisms: An In vitro study - P K Asmin; Christa Jose; Nusrath Fareed (Wolters Kluwer Medknow Publications, 2024)
Purpose: Oral candidiasis is one of the most common fungal opportunistic infections in the mouth caused by a fungus called Candida, and it presents as commensals in all humans. Over the last few decades, the increasing incidence of Candida infections parallels the growing numbers of immunocompromised patients. This trend is aggravated by the fact that there is a reckless use of antifungals. To combat this trend, the use of natural antifungals which have fewer side effects is recommended. Black grape seed extract (GSE) has shown a promise in this regard. Materials and Methods: Candida species such as Candida krusei, Candida glabrata, Candida tropicalis, and Candida albicans were used in the study. Fungal strains were passaged in the agar Sabouraud dextrose environment from 24 h to have live and fresh strains for the test. Black GSE was obtained. Minimum inhibitory concentration (MIC), of GSE, amphotericin B and fluconazole drugs on the included fungi was examined using disc diffusion method. Then, the plates were incubated for 24 h at 37°C. Finally, growth inhibitory zone was examined. Results: The analysis of the results revealed that the growth of C. albicans and C. krusei had been stopped at the concentration of 6.25 μg/mL, but the growth of C. glabrata and C. tropicalis was inhibited at a concentration of 12.25 μg/mL and 0.8 μg/mL respectively. Conclusion: The results obtained from the present study showed that both disc diffusion method and the maximum inhibitory concentration of MIC (Macro dilution) confirms the antimicrobial susceptibility of four species of candida to GSE. We conclude the possibility of GSE as an effective alternative measure for commercial antifungal agents, especially among immunocompromised patients, However, more laboratory and clinical studies need to be conducted to validate our findings.